Non-Ionizing Radiation as Threat in Everyday Life: A Review - Roslan, Umar; Fatin Syaza, Shariff Khan; Nor Hazmin, Sabri; Azmin, Hassan; Nor Shahida, Abd Mutalibd; Ahmad Nazri, Dagang; Hajar, Jaafar (2016)
Electromagnetic field (EMF) is a field of combination between electric and magnetic field. While electromagnetic radiation (EMR) can be divided into ionizing and non-ionizing radiation. This article review of published scientific studies about non-ionizing radiation and its effect on human body. This paper tend to create awareness for public that non-ionizing radiation provide an adverse effect towards public since its source is within our everyday life. For future study, we suggest for a policy to be apply at Malaysia as a basic guideline for EMR exposure and an implementation of mapping for EMR exposure at East and West of Malaysia to create an easiness for future researcher do a research in EMR field study.